2016
DOI: 10.3897/zookeys.563.6404
|View full text |Cite
|
Sign up to set email alerts
|

First Alaskan records and a significant northern range extension for two species of Diplura (Diplura, Campodeidae)

Abstract: Species in the class Diplura are recorded from Alaska for the first time. Two species, Tricampa rileyi Silvestri from Dall and Prince of Wales Islands in the Alexander Archipelago of Southeast Alaska and Metriocampa allocerca Conde & Geeraert from near Quartz Lake, southeast of Fairbanks, both in the family Campodeidae, are documented based on recently collected specimens deposited in the University of Alaska Museum Insect Collection. A brief review of the history of the documentation of the Alaskan soil micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Vertebrate and invertebrate distribution extension records are not uncommon across the Americas and are mainly based on studies of Natural Reserve Areas (Pereira, 2010;Gregory et al, 2015;Pachelle et al, 2015;Medina et al, 2016;Sikes & Allen, 2016). This is also the case in Ecuador, where most field studies on Chiroptera were conducted in areas belonging to the National System of Protected Areas (Baker et al, 2009;Loaiza-S, 2010;Moratelli & Wilson, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Vertebrate and invertebrate distribution extension records are not uncommon across the Americas and are mainly based on studies of Natural Reserve Areas (Pereira, 2010;Gregory et al, 2015;Pachelle et al, 2015;Medina et al, 2016;Sikes & Allen, 2016). This is also the case in Ecuador, where most field studies on Chiroptera were conducted in areas belonging to the National System of Protected Areas (Baker et al, 2009;Loaiza-S, 2010;Moratelli & Wilson, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This likely explains the hundreds of potentially endemic, mostly flightless, arthropod species in Alaska (Sikes & Allen 2016). Additionally, Alaska's former connection to Asia via the Bering Land Bridge has resulted in many complex and interesting biogeographic patterns between the Nearctic and Palearctic.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is clear that new regional records (Scudder and Sikes 2014;Sikes and Allen 2016) and species new to science (e.g. Sikes and Stockbridge 2013;Williams et al 2016) are continually being found on an annual basis, suggesting that the inventory of the entomofauna is far from complete.…”
Section: Historic Versus Modern Data -Bees and Butterfliesmentioning
confidence: 99%
“…This allowed organisms to survive in ice-free refugia (e.g., Beringia) (Abbott and Brochmann 2003;Behan-Pelletier and Schatz 2011;Elias and Brigham-Grette 2013;Pringle 2014). This is thought to be a primary explanation for Alaska's hundreds of potentially endemic arthropod species (Sikes and Allen 2016). Due to changes in climate and sea levels, the region acted alternatively as a passageway or a barrier, which has resulted in multiple dispersal events between the Palearctic and Nearctic across the Bering Land Bridge (Sanmartín et al 2001;Vila et al 2011;Sikes and Venables 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation